Pengaruh EMO DEMO Pemberian Makan Bayi Dan Anak (PMBA) Terhadap Peningkatan Pengetahuan Ibu Sebagai Upaya Pencegahan Stunting Pada Balita Di Posyandu Rangkaian Melati - Yulita, Yulita; Jairani, Eka Nenni; Nababan, Agnes Sry Vera (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
The problem of stunting does not only occur in Indonesia, but is also a global issue. The high rate of stunting in children under 5 years of age requires serious attention because it can affect their growth and development. Infant and young child feeding practices (PMBA) have great benefits in preventing stunting and supporting optimal growth and development processes. Inappropriate feeding in infants and toddlers can be one of the factors causing growth and development disorders known as stunting. This study aims to determine the effect of infant and young child feeding through emo-demo as an effort to prevent stunting in toddlers. The type of research is a quasi-experiment, with a one-group pretest-posttest design with a sample size of 30 mothers of toddlers. The results showed that there was an increase in the median score of maternal knowledge before and after being given an emo demo with a P-value of 0.000. The conclusion is that there is an effect of the emo demo about MP-ASI on changes in maternal knowledge before and after being given an emo demo at Posyandu.